Increases of antibiotic resistance in excessive use of antibiotics in smallholder dairy farms in northern thailand - W. Suriyasathaporn (2018)
Antibiotic resistance patterns of bacterial isolates from both quarter teat-tip swabs and their quarter milk samples were evaluated in smallholder dairy farms in northern Thailand with excessive use of antibiotics (HIGH) compared with normal use (NORM). Results from teat-tip swab samples showed that the percentage of Bacillus spp. resistance to overall antibiotics was significantly lower in the NORM group than that of the HIGH group, whereas, the resistance percentage of coagulase-negative staphylococci in the NORM group was higher than that of the HIGH one. The overall mastitis-causing bacteria isolated from milk samples were environmental streptococci (13.8%), coagulase-negative staphylococci (9.9%), Staphylococcus aureus (5.4%), and Corynebacterium bovis (4.5%). Both staphylococci and streptococci had significantly higher percentages of resistance to cloxacillin and oxacillin in the HIGH group when compared to the NORM one. An occurrence of vancomycin-resistant bacteria was also observed in the HIGH group. In conclusion, the smallholder dairy farms with excessive use of antibiotics had a higher probability of antibiotic-resistant pattern than the farms with normal use.